Good Environmental Governance Roles in Sustainable Solid Waste Management in Indonesia: A Review - Fariz, Reza Darma Al; Muis, Ramdiana; Anggraini, Nani; Rachman, Indriyani; Matsumoto, Toru (Department of Environmental Engineering - Universitas Pasundan - Indonesia, 2024)
Indonesia is an archipelagic country consisting of more than 17,500 islands. Urbanization and community agglomeration in urban areas in Indonesia are increasing the complexity of solid waste management in Indonesia. The old paradigm of 'collect-transport-disposal' waste management still occurs frequently in cities in Indonesia. This research is designed to be a systematic qualitative review. The relationships between good environmental governance and sustainable solid waste management are synthesized from a perspective of current conditions in Indonesia. The solution to sustainable waste management is generally carried out through well-organized waste management in an integrated manner from upstream to downstream with a 'cradle-to-grave' mindset, including the impacts that may arise therein. Implementing sustainable solid waste management requires commitment and support from all aspects of stakeholders. Good environmental governance is a comprehensive, dynamic, and complex concept that attempts to improve environmental conditions while promoting sustainable solid waste management. The results show that good environmental governance is very influential for sustainable solid waste management, but it still needs to be implemented optimally in Indonesia. Integration and synchronization of policies between the central government and local government must be further improved to implement good environmental governance.